2019
DOI: 10.1002/dvg.23344
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin and MucXS release by small secretory cells depend on Xpod, a SSC specific marker gene

Abstract: Summary Mucus secretion and ciliary motility are hallmarks for muco‐ciliary epithelia (MCE). Both, mammalian airways as well as the less complex epidermis of Xenopus embryos show cilia‐driven mucus flow to protect the organism against harmful effects by exogenous pathogens or pollutants. Four cell types set up the epidermal MCE in Xenopus. Multi‐ciliated cells (MCCs) generate an anterior to posterior flow of mucus. Ion secreting cells (ISCs) are characterized by the expression of ion transporters, presumably t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…To date, very few SSC markers have been described and they are either transcription factors such as Foxa1, or allow the detection of secreted compounds (Otogelin-like, HNK1, IPTKb, serotonin, Xpod) (Dubaissi et al, 2014; Kurrle et al, 2020; Walentek et al, 2014). Thus Crb3.S is, so far, the sole transmembrane protein described to be highly expressed in SSCs.…”
Section: Discussionmentioning
confidence: 99%
“…To date, very few SSC markers have been described and they are either transcription factors such as Foxa1, or allow the detection of secreted compounds (Otogelin-like, HNK1, IPTKb, serotonin, Xpod) (Dubaissi et al, 2014; Kurrle et al, 2020; Walentek et al, 2014). Thus Crb3.S is, so far, the sole transmembrane protein described to be highly expressed in SSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, inhibition of NICD transcriptional activity by a dominant-negative DNA-binding mutant of the CSF/RBPJ homolog SuH (SuH-DBM) or a dominantnegative form of Mastermind leads to excessive production of ionocytes and MCCs, while overexpression of a constitutive active NICD suppresses ionocyte and MCC specification [Deblandre et al, 1999;Stubbs et al, 2006;Quigley et al, 2011;Walentek, 2018]. It was further shown that overexpression of intermediate NICD levels in Xenopus increases the number of SSCs, that is, a secretory cell type that also produces mucins [Walentek, 2018;Kurrle et al, 2020]. Similarly, data from the mouse airway demonstrated that low Notch levels lead to specification of MCCs, while high Notch levels promote the production of club secretory cells [Guseh et al, 2009;Tsao et al, 2009].…”
Section: Notch Signalingmentioning
confidence: 99%
“…More data are also needed regarding the Notch regulation of ionocytes in the mammalian lung as in contrast to the Xenopus epidermis, where this cell type was initially described, Notch inhibition was shown to negatively affect ionocyte abundance [Quigley et al, 2011;Plasschaert et al, 2018]. Conversely, SSCs that share the characteristic serotonin production and secretion with mammalian PNECs are dependent on high Notch signaling in the frog, and the opposite is true for mouse PNECs, which are increased in numbers upon developmental deletion of multiple Notch receptors in the epithelium [Morimoto et al, 2012;Walentek, 2018;Kurrle et al, 2020]. In Xenopus, Notch inhibition was also shown to lead to downregulated expression of ∆N-TP63, while in the mammalian airways, Notch seems largely dispensable for BCs, and elevated Notch is required for differentiation of luminal epithelial cell types [Rock et al, 2011;Sirour et al, 2011].…”
Section: Notch Signalingmentioning
confidence: 99%
“…ISCs are specified by Foxi1, and are subdivided into α‐ and β‐ISCs by expression of Ubp1 in β‐ISCs, which is regulated by Notch signaling as well (Quigley et al, 2011). SSCs are specified by Foxa1 and require higher Notch levels as compared to ISCs and MCCs (Dubaissi et al, 2014; Kurrle, Kunesch, Bogusch, & Schweickert, 2020; Walentek, 2018; Walentek et al, 2014). After cell fate acquisition, cells insert apically into the epithelial layer.…”
Section: The Xenopus Embryonic Mucociliary Epidermismentioning
confidence: 99%
“…A similar mechanism could regulate the apical expansion in ISCs as they also contain an F‐actin rich surface. SSCs, which are specified and emerge slightly later than ISCs and MCCs, do not seem to have such an active expansion mechanism, but rely on the production of secretory vesicles for expansion of their apical surface, which strongly increases until premetamorphosis stages (Kurrle et al, 2020; Walentek et al, 2014) (Figures 1 and 2).…”
Section: The Xenopus Embryonic Mucociliary Epidermismentioning
confidence: 99%